THE POTENTIAL OF BIDAI WEBBING AS A SUPERIOR PRODUCT IN BENGKAYANG REGENCY BASE ON LOCAL WISDOM - rianti, reny; Edy Agustinus; Gustaf Hariyanto (JURNAL BORNEO AKCAYA, 2019)
Bidai webbing is a craft product that is produced through the indigineous skills of the Dayak Bidayuh people. With the One Village One Product appraisal approach, this study qualitatively assesses the potential of splinting to be pushed into a superior product, especially in order to support the development of the creative economy in Bengkayang Regency. By conducting in-depth interviews with informants who were determined by purposive sampling, it was found that splint webbing only achieved a score of 69.8 out of a total value of 100 or was in the 2 star classification (**), where Bidai webbing still requires basic guidance, but has the opportunity to increase as 3 star with various improvements. Even though the resulting splint has undergone innovations in terms of design and size, there are several obstacles that are often faced. The constraints referred to include: the scarcity of raw material, especially the raw material in the form of rattan, uncertainty of consumers and markets, as well as very simple finishing and packaging. As a result, the number of craftsmen shows a decreasing trend every day. This is considered to be a threat to the preservation of local wisdom of bidai webbing and the difficulty of encouraging it to become a superior product in Bengkayang Regency. Therefore, the participation of stakeholders is needed to maintain the availability of raw materials and increase the capacity of craftsmen and woven products through training for craftsmen and future generations. In addition, stakeholder support is needed to be involved in maintaining consistency in promotions and building relationships at the local, regional and international levels.